Can Ancient Philosophy Teach Us Anything? - Paczkowski, Przemysław (Sensus Historiae, 2023)
Ancient philosophy of man—various theories of happiness, virtue, moral education, political system etc.—based on the idea of human nature. This idea has been rejected by contemporary philosophical thought. But at the same time we use in different areas (psychology, coaching, education, politics etc.) many practical sciences which ancient philosophers had offered us. Why? In the article I try to justify the claim that ancient philosophy still teach us something about the man. The main argument is the analysis of Greek idea of human nature, based on the concept of dýnamis.